Rhizobium Inoculants Mitigate Corn Herbicide Residual Effects on Soybean Germination - Ncomiwe Maphalala; Alaina Richardson; Sabrina Quevedo Sastre; Aricia Ritter Correa; Fernanda Reolon de Souza; Te Ming Tseng (Seeds)
Corn residual herbicides offer a practical approach to comprehensive weed management throughout the growing season. However, the use of residual pre-emergence herbicides can have a negative impact on crops grown in succession or within a rotation. A study was carried out to determine the effect of the residual activity of selected corn herbicides on soybeans. The objective of the study was to evaluate the impact of these herbicides on the germination of inoculated soybean seeds. Experiments were conducted in greenhouse conditions to check the carryover effect on soybean germination. Treatment combinations of two pre-herbicides and two inoculants were applied: atrazine (2241 g ai ha−1), mesotrione (105 g ai ha−1), and Bradyrhizobium japonicum, Bradyrhizobium japonicum + Bacillus subtilis, respectively. A randomized complete block design evaluated six treatment combinations, including the control. All treatments, except uninoculated treatments, presented efficacy in reducing the carryover effects of corn residual herbicides on the germination of soybeans. An increase in final germination percentage was observed with Bradyrhizobium japonicum + Bacillus subtilis co-inoculation plus atrazine (24% increase) and Bradyrhizobium japonicum plus mesotrione treatment combinations (19% increase). Inoculating soybean seeds with rhizobium bacteria can reduce the carryover effects on the germination of soybean seeds grown in soil applied with atrazine and mesotrione.